Rehab Concepts and Discharge Dispositions: Workshop for Medical Students - Jeannine Nonaillada (Association of American Medical Colleges, 2018)
Introduction Safe transitions of care are an essential component of safety and quality for the patient community. It is imperative that providers choose appropriate discharge settings to reduce avoidable hospital readmissions. Additionally, providers must also ensure that the multifaceted needs of each patient are met with every discharge recommendation. There is often a lack of formal instruction in medical school on the various discharge dispositions, indications for rehab, and clinical indications for each setting. This is problematic for new interns who are tasked with entering discharge orders and relaying critical information between lead physicians and the interprofessional team. Methods A 60-minute workshop with both didactic and experiential components provided medical students with opportunities to gain an overview of discharge dispositions while also exercising critical thinking using case examples. The workshop was part of a 2-week Transition to Residency course at a single institution. Results Twenty-two fourth-year medical students participated in the workshop. Following the workshop, 100% of the participants stated that they had learned something new and that they intended to use the content in practice as interns. Subjective responses indicated that workshop content ought to be incorporated earlier in medical training. Discussion These results suggest that a 60-minute workshop including didactic instruction as well as experiential and inquiry-based learning can impact medical student knowledge and intent for practice change in regard to providing safe transitions of care for the patient community.